2013
DOI: 10.3945/ajcn.112.051128
|View full text |Cite
|
Sign up to set email alerts
|

Effect of acute and chronic red wine consumption on lipopolysaccharide concentrations

Abstract: Chronic RW consumption increases Bifidobacterium and Prevotella amounts, which may have beneficial effects by leading to lower LPS concentrations. This trial was registered at controlled-trials.com as ISRCTN88720134.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
54
1
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(59 citation statements)
references
References 51 publications
2
54
1
2
Order By: Relevance
“…Consistent with diets for CVD prevention (Eckel et al, 2013) and other dietary indices [e.g., Healthy Eating Index, Diet Quality Index (Kourlaba & Panagiotakos, 2009)], conceptual weights were assigned prior to averaging into a dietary quality index, Healthy Eating Preference Index (HEPI): fruits/vegetables (+3), protein (+1), fat (−3), sweets (−3), salty food (−3), wine (+2), and variety score (+2). Specific to red wine, moderate consumption is part of Mediterranean diet that associates with favorable effects on cardiovascular risk factors (Rees, et al, 2013), possibly through improved glucose metabolism (Chiva-Blanch et al, 2013) and lipopolysaccharide concentrations (Clemente-Postigo et al, 2013). The averaging liking for wine in the current study suggested that most participants were moderate drinkers.…”
Section: Methodsmentioning
confidence: 99%
“…Consistent with diets for CVD prevention (Eckel et al, 2013) and other dietary indices [e.g., Healthy Eating Index, Diet Quality Index (Kourlaba & Panagiotakos, 2009)], conceptual weights were assigned prior to averaging into a dietary quality index, Healthy Eating Preference Index (HEPI): fruits/vegetables (+3), protein (+1), fat (−3), sweets (−3), salty food (−3), wine (+2), and variety score (+2). Specific to red wine, moderate consumption is part of Mediterranean diet that associates with favorable effects on cardiovascular risk factors (Rees, et al, 2013), possibly through improved glucose metabolism (Chiva-Blanch et al, 2013) and lipopolysaccharide concentrations (Clemente-Postigo et al, 2013). The averaging liking for wine in the current study suggested that most participants were moderate drinkers.…”
Section: Methodsmentioning
confidence: 99%
“…The relative richness of Prevotella spp. and Prevotellaceae is frequently modulated following dietary interventions (49,50) and, in general, by lifestyle modifications (51), suggesting that these microorganisms represent active and rapidly reacting components of the human intestinal microbiota (37). Notably, Prevotella spp.…”
Section: Discussionmentioning
confidence: 99%
“…In separate work involving a singular traditional food or medicinal agent, the anti-inflammatory botanical Sophora flavescens, researchers, again using LPS as the inducing agent, found a more pronounced anti-inflammatory and antioxidant activity with the fermented form [151]. Recently red wine has been shown to increase Bifidobacterium levels, which in turn correlates with lower serum LPS concentrations [152]. Fermented grape pomace yields more total antioxidants and antioxidant activity than its unfermented counterpart [153].…”
Section: The Potential Of Fermented Foodsmentioning
confidence: 99%